The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1109/tasl.2013.2281574
|View full text |Cite
|
Sign up to set email alerts
|

Objective Intelligibility Measures Based on Mutual Information for Speech Subjected to Speech Enhancement Processing

Abstract: We propose a novel method for objective speech intelligibility prediction which can be useful in many application domains such as hearing instruments and forensics. Most objective intelligibility measures available in the literature employ some kind of signal-to-noise ratio (SNR) or a correlation-based comparison between the spectro-temporal representations of clean and processed speech. In this paper, we investigate the speech intelligibility prediction from the viewpoint of information theory and introduce n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…A typical scale is the ERB (equivalent rectangular bandwidth) scale, e.g., [18], [19]. It is natural, e.g., [15], to consider the auditory-domain signal to have one independent component signal per ERB. Auditory models provide a manner of deriving such component signals.…”
Section: A Model With Production and Interpretation Noisementioning
confidence: 99%
See 2 more Smart Citations
“…A typical scale is the ERB (equivalent rectangular bandwidth) scale, e.g., [18], [19]. It is natural, e.g., [15], to consider the auditory-domain signal to have one independent component signal per ERB. Auditory models provide a manner of deriving such component signals.…”
Section: A Model With Production and Interpretation Noisementioning
confidence: 99%
“…The interpretation process for speech is also noisy: speech signals that are ambiguous in their pronunciation may be interpreted in various ways. Information theoretical concepts have been used in the analysis of human hearing [14] and for the definition of measures of intelligibility [15]. These models do not have the notion of production noise, but the model of [14] considers sensory noise, which corresponds to our interpretation noise.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, information theory (IT) has been proposed as a new paradigm for speech intelligibility prediction [13,14,15]. This is a natural approach to take given that the fundamental goal of speech communication is to transfer information from a talker to a listener.…”
Section: Introductionmentioning
confidence: 99%
“…The STOI measure is based on the sum of the correlation between the envelopes of the clean speech signal and the corrupted speech measured with 15 1/3-octave frequency bands starting at 150 Hz. More recently, using the same frequency bands, it has been shown that a mutual information-based measure can perform better than STOI (Taghia and Martin, 2014).…”
Section: Objective Intelligibility Measuresmentioning
confidence: 99%